Fragmentation of pure and hydrated clusters of 5Br-uracil by low energy carbon ions: observation of hydrated fragments. Issue 30 (28th June 2017) - Castrovilli, M. C.; Markush, P.; Bolognesi, P.; Rousseau, P.; Maclot, S.; Cartoni, A.; Delaunay, R.; Domaracka, A.; Kočišek, J.; Huber, B. A.; Avaldi, L.
Abstract : The fragmentation of the isolated 5-bromouracil (5BrU) molecule and pure and nano-hydrated 5BrU clusters induced by low energy 12 C 4+ ions has been studied. Abstract : The fragmentation of the isolated 5-bromouracil (5BrU) molecule and pure and nano-hydrated 5BrU clusters induced by low energy 12 C 4+ ions has been studied. A comparison indicates that the environment, on the one hand, protects the system against the complete break-up into small fragments, but, on the other hand, triggers 'new' pathways for fragmentation, for example the loss of the OH group. The most striking result is the observation of several series of hydrated fragments in the hydrated cluster case, with water molecules bound to hydrophilic sites of 5BrU. This highlights the strong interaction between 5BrU and water molecules and the blocking of specific fragmentation pathways, such as the loss of the BrC2 H group for example.